An Analysis of Heat Flow Through a Borehole Heat Exchanger Validated Model - Florides, Georgios A.; Pouloupatis, Panayiotis; Christodoulides, Paul (My University, 2012)
Earth heat exchangers are essential parts of the ground-source heat pumps and the accurate prediction of their performance is of fundamental importance. This paper presents the development and validation of a numerical model for the simulation of energy flows and temperature changes in and around a borehole heat exchanger when a fluid circulates through a U-tube. Based on the time-dependent convection-diffusion equation, the FlexPDE software package is employed to solve the resulting boundary value problem that model a heat exchanger. First, the mathematical model is validated through a comparison with data obtained from experiments with real borehole set-ups in Cyprus. Then the validated model is used to study the heat flow and the temperature variation in the heat-exchanger. Finally conclusions are extracted on how various parameters like the U-tube diameter, the variation of the ground thermal conductivity and specific heat and the borehole filling material affect the temperature of the inlet and outlet fluid.
Keywords: Mathematical models; Heat exchangers; Heat--Convection; Computer simulation; Thermal conductivity